VHDL DESIGN FOR IMAGE SEGMENTATION USING LOG GABOR FILTER FOR DISEASE DETECTION - Gomathi, P.R.; Arun, A. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Tonsillitis, Tumor and many more skin diseases can be detected in its early-state and can be cured. For this a new idea for efficient Gabor filter design with improved data transfer rate, efficient noise reduction, less power consumption and reduced memory usage is proposed in this paper. The filter design is suitable for detecting the early stages of disease using textural properties of anatomical structures. The code for Log Gabor filter will be developed in VHDL using Modelsim and then implemented on SPARTAN-3E FPGA kit. These systems must provide both highly accurate and extremely fast processing of large amounts of image data.